Using Wavelet Transform To Extract Frequency Content In Electric Field Radiated By Unusual Lightning Activity - Neupane, Suraj; Sharma, Shriram; Sharma, Puja (Scientific World, 2021)
In this frequency spectrum electric fields radiated by the unusual lightning activities have been computed using the wavelet transform technique. The unusual lightning activities have very recently been identified activities and are very poorly understood among the lightning community. As the electric fields are very recently identified and are measured in time domain, to the best of our knowledge, their frequency content has not been studied as of today. To understand the physics of the discharge mechanism of such events, the frequency domain information plays a significant role. In order to extract frequency domain information from the time domain electric field signatures the wavelet transform technique has been employed. For the purpose, the electric field pertinent to the unusual activity, has been divided into two parts namely main activity and the preceding opposite polarity field change. From the computation, it is found that the opposite-polarity field change radiates energy in the spectral range of 2 kHz to 173 kHz whereas, the main activity predominantly radiates in the frequency range 2 kHz to 162 kHz. Such a wider spectral range that the unusual activities radiate have not been reported for the other known activities such as positive and negative return strokes. Evidently, the unusual events have some unique origin of discharge unlike the known activities. Further, as the unusual events were noticed in the temperate region (Uppsala, Sweden) and Sub-tropical climatic zone (Kathmandu, Nepal), it should have some common source of origin between two regions.